Penerapan Cognitive Behavior Therapy Untuk Mengatasi Fobia Sosial (Studi Kasus Pada Klien “Y” Di Desa Pedamaran) - Weldi Hansa; Bela Janare Putra (Journal of Society Counseling, 2023)
This thesis was published with the title "Application of Cognitive Behavior Therapy to Overcome Social Phobia (Case Study on Client "Y" in Pedamaran Village". The background of this study is characterized by social problems that can cause a person to experience social phobia and tend to make him avoid social situations and do not want to socialize with the surrounding environment. This study aims to find out how the condition of social phobia experienced by clients and how the strategy of Cognitive Behavior Therapy in overcoming social phobia. This research method uses a qualitative research method using the case study method and using a Cognitive Behavior Therapy approach, a data collection method using documentation, observation and interviews. The results of this study show that the reduced anxiety felt by clients when doing social interactions, starting to socialize with their social environment even clients are more courageous to interact with me at length and have begun to accept the situation indeed every change that occurs still needs a mentoring process so that fear and anxiety do not come and return to be felt by clients.